Nutritional value of hydrothermally processed Jatropha curcas kernel and its effect on growth and hematological parameters of Clarias gariepinus fingerlings (Burchell, 1822) - Sarah Ojonogecha Musa; Lateef Oloyede Tiamiyu; Shola Gabriel Solomon; Victoria Offuene Ayuba; Victor Tosin Okomoda (Aquaculture Reports, 2018)
The anti-nutritional components of Jatropha curcas have long limited the use of this unconventional feed ingredient in animal nutrition. In this study, the nutritional value of hydrothermally processed J. curcas kernel (JCK) meal in the diet of African catfish Clarias gariepinus (Burchell, 1822) was investigated. Upon processing in boiling water (100 °C) for 0, 30, 60, and 90 min, the nutritional characteristics of the JCK improved as the process was prolonged. However, many essential amino acids were reduced beyond 30 min of processing. Four isonitrogenous (35% CP) and isocaloric (315 kcal g−1) diets were then formulated with the inclusion of processed JCK at 29% and fed to the fingerlings of C. gariepinus for 56 days. The processed JCK performed better than the control diet. The optimal time of processing which gave the maximum weight gain (9 ± 0.54 g) was 62 mins using the second order polynomial regression analysis. The dietary inclusion of the processed JCK meal resulted in significant improvement in the blood parameters of the fish compared to those fed raw JCK. Similarly, the cost of feed and fish production was substantially reduced with inclusion of the processed JCK. It was therefore concluded that hydrothermal processing improved the nutritional profile of JCK and its dietary utilization by African catfish C. gariepinus fingerlings. Keywords: Anti-nutritional factors, Hydrothermal processing, African catfish, Unconventional feeds